Applications of Optical Fibers for Sensing - Christian Cuadrado-Laborde (IntechOpen, 2019)
In this book the reader will find a collection of chapters written by different research teams, describing different applications of optical fibers for sensing. This work is mainly addressed to researchers already working in this area, but it is also accessible to anyone with a scientific background who desires to have an updated overview of the recent progress in this domain. It will also be valuable to scientists and engineers who have become newly involved in this field. Each chapter is self-contained and can be read independently of the others. This book intends to provide highlights of the current research in this area, showing the recent advances in the field of optical fiber sensing.
English
Keywords: Physical Sciences; Engineering and Technology; Optoelectronics; Physics; Optics and Lasers